Tuberous sclerosis misdiagnosed as epilepsy (Bangladesh Medical Journal Khulna, 2014)
Tuberous sclerosis (TS) is a rare genodermatoses characterized by neurological symptoms and hamartomas in multiple organs including brain, skin, kidney, eyes, heart, lungs & G.I tract. The classic triad of epilepsy, adenoma sebaceum and mental retardation usually occurs in one third of the patients, thus requiring high index of suspicion to diagnose TS. Otherwise it may easily be misdiagnosed as epilepsy or neurofibromatosis. Here we present a case of tuberous sclerosis in 11 year old girl misdiagnosed as epilepsy because of her convulsions. A comprehensive medical history including family history, thorough physical examinations, clinical suspicion and neuroimaging are required to confirm the diagnosis. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18238 Bang Med J (Khulna) 2013; 46 : 31-33